Sulfamate Esters Guide C(3)-Selective Xanthylation of Alkanes - Ayer, Suraj K. (J Org Chem, 2019)
Owing to the pervasiveness of hydroxyl groups in natural isolates, alcohol derivatives are alluring directing groups. Herein, an alcohol-derived sulfamate ester guides the light initiated xanthylation of primary, secondary, or tertiary centers. This process enables formal directed deuteration, azidation, thiolation, and vinylation reactions.